«Revista Estudos Feministas»: uma trajetória de desafios - Cristina Scheibe Wolff (Storia delle Donne, 2020)
This article presents a history and an analysis of «Revista Estudos Feministas» («REF»), published by Federal University of Santa Catarina, in Brazil. «REF» is today the main journal in gender studies, feminisms and sexualities fields in Brazil, and one of the most important in Latin America. The article tells about its beginning, in Rio de Janeiro, and how it became published by Universidade Federal de Santa Catarina since 1999. To maintain a journal like «REF», with quality and frequency, imposes challenges that encompass technical issues and political matters, especially in contemporary Brazil. Feminist struggles continue in recent years and have acquired new intensity, which is reflected in the pages of the journal.